Efektivitas Cognitive Behavior Therapy (CBT) untuk Meningkatkan Kemampuan Coping pada Pelajar Pecandu Napza - Hanif Kurniawati; Budi Purwoko; Tamsir Muis (Indonesian Journal of Educational Counseling, 2021)
THE EFFECTIVENESS OF COGNITIVE BEHAVIOR THERAPY (CBT) TO IMPROVE COPING ABILITY IN DRUG ADDICT STUDENTS. This study provides an overview of the effect of Therapy with the Cognitive Behavioral Concept Approach to Preventing Relapse in Drug Abusers. The purpose of this study was to determine whether there is an effect of therapy with cognitive behavioral conceptual approaches to prevent relapse in drug abusers. The research design applied to the study was an experimental research design with a pretest and posttest control group design. The analysis used to see the significance of changes before and after the intervention was non-parametric analysis, namely the Two Independent Sample Test Mann Whitney U. The therapy process was carried out in 5 stages, with a total of 8 meetings, according to the meeting design in each stage. The results of therapy showed no significant difference between the experimental group and the control group.